Docetaxel induced interstitial pneumonitis: a case report - Taran, Rakesh; Bhandari, Virendra; Pant, Sidharth (International Journal of Basic & Clinical Pharmacology, 2017)
Incidence of diffuse alveolar damage is rarely seen after administration of docetaxel used alone or in combination with other chemotherapeutic drugs in absence of radiation. Here we present one such patient who developed diffuse alveolar pneumonitis after administration of first dose of docetaxel and the patient responded to steroids rather than antibiotics and antifungal drugs confirming the cause. This rapid onset drug induced alveolar pneumonitis illustrates that no therapeutic intervention is without its intrinsic and unanticipated risks.